Use the formula:
y2-y1
———
x2-x1
So for this problem it would be:
6-5
——
7-4
= 1
—
3
Hope this helped, if it did I would appreciate it if you would consider giving me brainliest!
Answer:
x= -1
y=2
Step-by-step explanation:
6x+5y=4
6x-7y=-20
Subtract
If we factorize the expression
![6x^4-9x^3-36x^2+54x](https://tex.z-dn.net/?f=%206x%5E4-9x%5E3-36x%5E2%2B54x%20)
We will get
![3x(2x-3)(x^2-6)](https://tex.z-dn.net/?f=3x%282x-3%29%28x%5E2-6%29)
Hope I helped!
Answer:
B = 129
Step-by-step explanation:
Opposite angles of a parallelogram are equal (or congruent)
A and C are both 51.
All angles in a parallelogram equal 360
Take both the known angles and substract from 360, than divide by 2.
B = (360 - 51 - 51)/2
B = 129
9x² + bx + 64
\/(9x²) = 3x
\/84 = 8
2*3x*8 = 48x
b = 48